Exponential expansionism: key contemporary challenges to immigration detention abolitionism - Bhatia, Monish (Handbook on border criminology, 2024)
The exponential increase in formal administrative immigration detention has been a worrying development for migrants and people working across migrant rights sectors internationally. These spaces have subsequently been a key focus for border and immigration detention abolitionists, and civil rights campaigners and organisations more broadly (including expansive work undertaken at Border Criminologies over the past decade). However, the means by which detention is being exercised contemporarily puts increased pressure on abolitionist objectives. Although formal administrative immigration detention centres are notoriously difficult to access and the corporatisation of detention has facilitated further expansion, more and more spaces are implemented into the border industrial complex which embed existential forms of confinement, but that are not visibilised or regulated in the same ways. Indeed, as this chapter argues, it is environmentally ‘softer’ approaches which can make the structural violence inherent to them even more difficult to pinpoint, and subsequently resist or challenge. In many countries and regions these include asylum centres; deportation centres; asylum barges; and even the detention of rescue ships, leaving migrants adrift at sea for days at a time. Alternatives to custody, which are increasingly dubbed as softer, cost-effective and preferable to ‘hard’ detention options, facilitate the net-widening and expansion of social controls. This includes electronic monitoring and geo-location tagging of migrants, including the use of facial recognition smartwatches for migrants who have been criminalised in the United Kingdom. This, we argue, creates new realms of existential confinement, and subsequently nuanced approaches for challenging and resisting insidious controls.